2003
DOI: 10.1046/j.1365-2672.2003.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory evaluation of three flagellin PCR/RFLP methods for typing Campylobacter jejuni and C. coli: the CAMPYNET experience

Abstract: This work should facilitate progress towards inter-laboratory standardization of fla typing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 29 publications
2
40
0
4
Order By: Relevance
“…PCR amplification was performed with a Ready-to-Go system (GE Healthcare, Little Chalfont, UK). RFLP-flaA with the restriction enzyme DdeI (Roche, Madrid, Spain) was performed following the Campynet protocol (Harrington et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification was performed with a Ready-to-Go system (GE Healthcare, Little Chalfont, UK). RFLP-flaA with the restriction enzyme DdeI (Roche, Madrid, Spain) was performed following the Campynet protocol (Harrington et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…These observations are largely consistent with data from large-scale comparative genomic studies that were compared to the C. jejuni NCTC11168 genome sequence (26) showing that significant regions of the C. jejuni genome are stable (32) but that as much as 21% of genes in NCTC11168 may be dispensable (8). More recently, an interlaboratory evaluation of three flagellin PCR/RFLP methods for typing C. jejuni and C. coli showed that analysis of the full flaA gene using the restriction endonuclease DdeI was an appropriate method for standardization, as demonstrated by 100% interlaboratory reproducibility (12). Collectively, these studies suggest that RFLP-flaA is a discriminatory, reliable, and relatively inexpensive typing tool for Campylobacter.…”
mentioning
confidence: 99%
“…For Campylobacter spp., amplified fragment length polymorphism methods are at least as discriminatory as multilocus sequence typing (MLST) and may be as discriminatory as PFGE (13,32); they are certainly less labor-intensive than PFGE (3). Flagellin locus restriction fragment length polymorphism (fla-RFLP) methods have been developed and have proved both epidemiologically relevant and very useful for strain discrimination in an outbreak analysis (14,21,22,23,25). Analysis of the flagellin short variable region (fla-SVR) yielded results very similar to those obtained by sequencing of the entire gene (21).…”
mentioning
confidence: 99%